2009
DOI: 10.1148/radiol.2503081154
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion Hemorrhage Following Acute Myocardial Infarction: Assessment with T2* Mapping and Effect on Measuring the Area at Risk

Abstract: Research ethics committee approval and informed consent were obtained. The purpose of this study was to assess the feasibility of multiecho T2* mapping of the heart for detecting reperfusion hemorrhage following percutaneous primary coronary intervention (PPCI) for acute myocardial infarction, and to measure the effect of hemorrhage on quantifying the ischemic area at risk (IAR) on T2-weighted magnetic resonance images. Fifteen patients (mean age, 59 years; 13 men, two women) were imaged a mean of 3.2 days fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 35 publications
4
79
0
Order By: Relevance
“…On the basis of patient and proof-of-concept animal studies, we showed that acute reperfusion myocardial hemorrhage is better characterized with T2*-based cardiac MR imaging than it is with T2-based cardiac MR imaging. This observation is consistent with previous reports, which have suggested that hemorrhage and edema have counteracting influences on T2 (and T2-weighted) images (16,30,32). It is expected that our findings here can be instrumental in furthering our understanding of the role of reperfusion hemorrhage in patients.…”
Section: Cardiac Imaging: Acute Reperfusion Myocardial Hemorrhagesupporting
confidence: 93%
“…On the basis of patient and proof-of-concept animal studies, we showed that acute reperfusion myocardial hemorrhage is better characterized with T2*-based cardiac MR imaging than it is with T2-based cardiac MR imaging. This observation is consistent with previous reports, which have suggested that hemorrhage and edema have counteracting influences on T2 (and T2-weighted) images (16,30,32). It is expected that our findings here can be instrumental in furthering our understanding of the role of reperfusion hemorrhage in patients.…”
Section: Cardiac Imaging: Acute Reperfusion Myocardial Hemorrhagesupporting
confidence: 93%
“…[15][16][17][18] Although histological proof of the specificity of hypointense cores for IMH is still awaited, hypointense core regions of infarcted myocardium in T2-weighted and T2*-weighted CMR have been associated with hemorrhagic infarcts, because breakdown products of hemoglobin have paramagnetic effects and thereby shorten T2-relaxation times. [7][8][9][10][11]13,14,19,20 Thus, CMR might be a powerful tool to assess the occurrence and extent of reperfusion injury in humans and to determine its relation to the AAR, salvaged myocardium, infarct size, and MO.…”
Section: Clinical Perspective On P 362mentioning
confidence: 99%
“…11 The technique of T2* imaging has been validated histopathologically in animal and ex vivo studies as an effective method for quantifying reperfusion hemorrhage as well as myocardial iron overload and has been successfully applied in humans. 11,14,28 -31 Advantages of T2*-CMR include its more sensitive detection of the susceptibility effects of IMH than spin-echo imaging.…”
Section: Hypointense Infarct Core In T2-weighted Cmrmentioning
confidence: 99%
“…T2* CMR has been shown to identify myocardial hemorrhage in acute infarction. 58 Early gadolinium enhancement is also superior to echocardiography for the identification of ventricular thrombi, which appear as dark filling defects on the endocardial surface of enhanced infarcts. 59 Myocardial fiber microstructure remodeling after infarction can also be studied with diffusion tensor tractography.…”
Section: Myocardial Infarctionmentioning
confidence: 99%